2009
DOI: 10.1007/978-0-387-95857-6_10
|View full text |Cite
|
Sign up to set email alerts
|

On the Problem of Synchronization of Identical Dynamical Systems: The Huygens’s Clocks

Abstract: In 1665, Christiaan Huygens reported the observation of the synchronization of two pendulum clocks hanged on the wall of his workshop. After synchronization, the clocks swung exactly in the same frequency and 180 o out of phaseanti-phase synchronization. Here, we propose and analyze a new interaction mechanism between oscillators leading to exact anti-phase and in-phase synchronization of pendulum clocks, and we determine a sufficient condition for the existence of an exact anti-phase synchronization state. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…However, Czolczynski et al [5] later confirmed co-existence of both regimes experimentally using modern clocks with non-impulsive escapements. Numerical simulations in [6,7] also show co-existence for some parameter values. The common trait in all three cases is that the escapements involved do not have an engagement threshold.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, Czolczynski et al [5] later confirmed co-existence of both regimes experimentally using modern clocks with non-impulsive escapements. Numerical simulations in [6,7] also show co-existence for some parameter values. The common trait in all three cases is that the escapements involved do not have an engagement threshold.…”
Section: Introductionmentioning
confidence: 74%
“…The corresponding linear generating system (see Appendix for the terminology) is obtained by setting µ = 0 in (6). Poincaré theorem gives sufficient conditions for existence and stability of periodic solutions to the original non-linear system that converge to periodic solutions of the generating system when µ → 0.…”
Section: Small Damping In the Framementioning
confidence: 99%
“…enforces the synchronization objective given in Eq. (12). Furthermore, if conditions (36) are satisfied, then the synchronous solution (12) is locally asymptotically stable.…”
Section: Stability Of the Desired Synchronous Solutionmentioning
confidence: 99%
“…Likewise, there are works, see, e.g., [10][11][12][13][14], in which it has been demonstrated that the damping in the system has a strong influence on the type of synchronization: for relatively large damping the pendula tend to synchronize in anti-phase, whereas for relatively small damping the pendula 'prefer' to synchronize in-phase.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation